Research progress of the engagement of inorganic nanomaterials in cancer immunotherapy - Tingwei Peng; Tianzhao Xu; Xinghui Liu (Taylor & Francis Group, 2022)
Cancer has attracted widespread attention from scientists for its high morbidity and mortality, posing great threats to people's health. Cancer immunotherapy with high specificity, low toxicity as well as triggering systemic anti-tumor response has gradually become common in clinical cancer treatment. However, due to the insufficient immunogenicity of tumor antigens peptides, weak ability to precisely target tumor sites, and the formation of tumor immunosuppressive microenvironment, the efficacy of immunotherapy is often limited. In recent years, the emergence of inorganic nanomaterials makes it possible for overcoming the limitations mentioned above. With self-adjuvant properties, high targeting ability, and good biocompatibility, the inorganic nanomaterials have been integrated with cancer immunotherapy and significantly improved the therapeutic effects.